Analisis Inovasi dalam Upaya Mempermudah Capaian Kinerja dan Data Potensi Kinerja Daerah Perkotaan - Wendrian Fadli; Muhammad Ro'uuf Fadhillah (Jurnal Studi Inovasi, 2021)
Since 2009, Indonesia has had its own laws and regulations as a standard for services to the community, so on July 18 2009 Indonesia passed Law No. 25 of 2009 on Public Services. This research uses a descriptive qualitative method that describes an objective state or certain event based on visible facts or as it should be, which is then accompanied by general conclusions based on these historical facts. The population in this study are cities that have made innovations in their regions, while the samples in this study are innovations made by Bekasi City and South Tangerang City which aim to analyze innovation in an effort to facilitate performance achievement and performance potential data. The results of this study are proven that as an important actor, the Regional Government according to its authority is expected to be able to produce appropriate decisions and actions to solve problems and meet the needs of the people in their regions. In line with this, we realize that serious efforts are needed to raise the quality of local government decisions and actions to be more effective and efficient through innovative breakthroughs. The results of E-Sipeng Kesbangpol's Innovation (Information Technology-Based Activity Implementation Control System and Performance Achievement of KESBANGPOL Agency) in Bekasi City in the short term, one of which is the formation of an effective team. Meanwhile, the innovation results that can be felt with the SIMPUS Innovation (Puskesmas Management Information System) in South Tangerang City, one of which is work effectiveness: Accelerating the process of health services to the community (eg registration from 7 minutes manually to 1 minute).